2016
DOI: 10.1111/acer.13163
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive Bias Modification Training During Inpatient Alcohol Detoxification Reduces Early Relapse: A Randomized Controlled Trial

Abstract: This is the first trial demonstrating the feasibility of CBM delivered during alcohol detoxification and supports earlier research suggesting it may be a useful, low-cost adjunctive treatment to improve treatment outcomes for alcohol-dependent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
114
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 34 publications
(47 reference statements)
8
114
2
1
Order By: Relevance
“…Another useful addition could be to include craving induction with imagery or stress manipulations (Sinha, ). In the current study, patients were already abstinent, and a previous study also found an effect of CBM during detoxification (Manning et al., ). It may be more useful to do an intervention while patients feel stronger automatic or subjective approach tendencies toward the alcohol.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Another useful addition could be to include craving induction with imagery or stress manipulations (Sinha, ). In the current study, patients were already abstinent, and a previous study also found an effect of CBM during detoxification (Manning et al., ). It may be more useful to do an intervention while patients feel stronger automatic or subjective approach tendencies toward the alcohol.…”
Section: Discussionsupporting
confidence: 68%
“…In these paradigms, relatively automatic responses are retrained into more beneficial reactions with computerized training. Several CBM studies (mostly with another variety of CBM: approach bias retraining) have shown positive findings in alcohol‐dependent populations (Eberl et al., ; Manning et al., ; Rinck et al., in press; Schoenmakers et al., ; Wiers et al., ). This clinical study focused on attentional bias modification (ABM), in which participants are trained to no longer focus attention on alcohol‐related stimuli.…”
mentioning
confidence: 99%
“…Approach biases are thought to play an important role in (the transition to) heavy drinking (Lindgren et al., ; Robinson & Berridge, ). Moreover, after training dependent individuals to avoid alcohol cues instead of approaching them, relapse rates decreased (Eberl et al., ; Kakoschke, Kemps, & Tiggemann, ; Manning et al., ; Rinck, Wiers, Becker, & Lindenmeyer, ; Wiers, Eberl, Rinck, Becker, & Lindenmeyer, ; Wiers, Ludwig, et al., ; Wiers, Stelzel, et al., ). Yet, such a re‐training has not been successful in undergraduate students in terms of reducing approach biases and drinking behaviour (Lindgren et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive training tasks have decreased alcohol approach bias in hazardous-drinking students (Wiers et al, 2010) and inpatients in alcohol treatment, who exhibited a 13% reduction in relapse (compared to a control group) one year after treatment (Wiers et al, 2011). These CBM results have been replicated (Eberl et al, 2013) and extended (Manning et al, 2016) by showing a 30% reduction in relapse two weeks after patients completed a seven-day alcohol detoxification program that included a course of active CBM training compared to controls in a sham training condition. While the outcomes from these studies suggest that ABM and CBM may be promising clinical tools, other authors have cautioned that more experimental evidence is required to clarify research results from studies that have failed to note similar effects (Christiansen et al, 2015; Cristea et al, 2016; Field et al, 2013; Schoenmakers et al, 2007; Wiers et al, 2013).…”
Section: Introductionmentioning
confidence: 82%